2019
DOI: 10.1128/mbio.00934-19
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Ergosterol Biosynthesis Modulates Activity of the Pdr1 Transcription Factor in Candida glabrata

Abstract: A crucial limitation in antifungal chemotherapy is the limited number of antifungal drugs currently available. Azole drugs represent the most commonly used chemotherapeutic, and loss of efficacy of these drugs is a major risk factor in successful treatment of a variety of fungal diseases. Candida glabrata is a pathogenic yeast that is increasingly found associated with bloodstream infections, a finding likely contributed to by its proclivity to develop azole drug resistance. C. glabrata often acquires azole re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 44 publications
6
64
0
Order By: Relevance
“…One of the two isolates with the FLZ MIC = 32 µg/mL harboured a unique novel mutation (L281V) (Figure 1, Tables 2 and 3, and Table ). Recent studies indicate that UPC2, a zinc cluster transcription factor, may contribute to FLZ resistance in C glabrata , 51,52 which may explain the high FLZ MIC for isolate G51 (32 µg/mL) without any exclusive amino acid changes in Pdr1p expected for this phenotype (Tables 2 and 3, and Table ). Although AFST did not reveal echinocandin resistance in vitro, previously reported mutations, including S629T 53 (in isolate G29 susceptible to both MCF and AND) and S663P 54 (in isolates G53 and G103 intermediate for susceptibility to MCF and AND), were detected in HS1‐Fks1 and HS1‐Fks2, respectively (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…One of the two isolates with the FLZ MIC = 32 µg/mL harboured a unique novel mutation (L281V) (Figure 1, Tables 2 and 3, and Table ). Recent studies indicate that UPC2, a zinc cluster transcription factor, may contribute to FLZ resistance in C glabrata , 51,52 which may explain the high FLZ MIC for isolate G51 (32 µg/mL) without any exclusive amino acid changes in Pdr1p expected for this phenotype (Tables 2 and 3, and Table ). Although AFST did not reveal echinocandin resistance in vitro, previously reported mutations, including S629T 53 (in isolate G29 susceptible to both MCF and AND) and S663P 54 (in isolates G53 and G103 intermediate for susceptibility to MCF and AND), were detected in HS1‐Fks1 and HS1‐Fks2, respectively (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, according to a recent study, chemical and/or genetic inhibition of histone acetyltransferase, Cgn5p, is lethal in C. glabrata isolates harboring GOF mutations in PDR1; it showed a significantly reduced frequency of GOF mutations in CGN5-inhibited C. glabrata isolates compared with non-inhibited C. glabrata isolates in an evolutionary model of FLZR [100]. It was recently shown that the mechanism of azole resistance in C. glabrata involves a complicated circuitry of zinc cluster transcription factors other than Pdr1, such as Upc2A (Figure 3) [105,106]. Interestingly, double deletion of Upc2A (upc2AΔ) in both fluconazole-susceptible and FLZR C. glabrata isolates results in a 16-fold decrease of FLZ MIC, and downregulation of CDR1, PDH1, and PDR1 upon induction by FLZ [106].…”
Section: Candida Glabratamentioning
confidence: 97%
“…It was recently shown that the mechanism of azole resistance in C. glabrata involves a complicated circuitry of zinc cluster transcription factors other than Pdr1, such as Upc2A (Figure 3) [105,106]. Interestingly, double deletion of Upc2A (upc2A∆) in both fluconazole-susceptible and FLZR C. glabrata isolates results in a 16-fold decrease of FLZ MIC, and downregulation of CDR1, PDH1, and PDR1 upon induction by FLZ [106].…”
Section: Candida Glabratamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key mechanisms that provide azole tolerance is the upregulation of PDR transporters that extrude xenobiotic compounds from cells (Prasad et al, 2015). An increase in azole resistance can be attributed to the upregulation or activation of these transporter proteins, which is triggered by sterol deficiency (Vu et al, 2019). To test whether azole tolerance in the LAM quadruple mutant is mediated by PDR transporters, we measured the accumulation of PDR substrates and the level of main ABC-transporter in the wild-type strain and in the Δlam1Δlam2Δlam3Δlam4 strain.…”
Section: C B Amentioning
confidence: 99%